Synthesis and biological evaluation of salicylaldimine complexes based on an alkylated PTA scaffold - Cassells, Irwin (Department of Chemistry, 2017)
Cancer remains one of the largest pandemics in the world, with millions affected by this disease every year. Since the discovery of the anticancer properties of cisplatin and other platinum-based drugs, metal-based chemotherapies have been extensively researched. Due to the elevated levels of toxicity of many platinum-based drugs, a rise in research using other metal-based drugs for the treatment of cancer has been observed. Of these, platinum group metals such as ruthenium, rhodium and iridium have shown great promise over the last several decades. RAPTA-type (ruthenium arene 1,3,5-triaza-7-phosphaadamantane) complexes have shown great promise in vivo for the treatment of certain cancers. Combining RAPTA with other biologically active groups has often resulted in increased potency and selectivity against various cancer cells in vitro. In this study, we investigated the synthesis, characterisation and biological evaluation of salicylaldimine complexes with an alkylated PTA scaffold. All of the metal complexes were screened for their activity against MCF7 breast cancer cells in vitro, in addition, the most active complexes were screened against Chinese Hamster Ovarian (CHO) non-cancerous cells to evaluate their selectivity. A series of salicylaldimine ligands, as well as a benzyl alkylated PTA scaffold were prepared. Complexes of these ligands were synthesised by a reaction with [RuCl(µ-Cl)(p-cymene)]₂, [RhCl(µ-Cl)(Cp*)]₂ or [IrCl(µ-Cl)(Cp*)]₂. In addition to this, new PTA containing analogues of these neutral complexes were also prepared by reacting the afore mentioned salicylaldimine complexes with the alkylated PTA scaffold. All the compounds were characterised using an array of techniques including NMR spectroscopy, IR spectroscopy and mass spectrometry. Single crystal X-ray diffraction (XRD) was used to confirm the bidentate coordination mode of the salicylaldimine ligand to the metal centre, as well as the presence of the metal-phosphorus bond for the alkylated PTA complexes. All of the metal complexes were evaluated against the MCF7 breast cancer cell line. The ruthenium and iridium salicylaldimine complexes showed comparable or greater cytotoxicity than cisplatin at 20 µM against the MCF7 cancer cells, as well as greater cytotoxicity than their rhodium counterparts. Three of the salicylaldimine complexes exhibited potent activity (18 < IC₅₀ < 21 M). Selectivity studies showed that two of these complexes had a greater affinity for cancerous cells than for the CHO non- cancerous cells. All the alkylated PTA complexes were less cytotoxic than cisplatin against the MCF7 cancer cells. Preliminary mechanistic studies of the most active complexes suggest ruthenium undergoes solvation prior to 5'-GMP binding, whereas iridium was inert to the solvation process.